Studying solutions at high shear rates: a dedicated microfluidics setup. (12th February 2016) - Wieland, D. C. F.; Garamus, V. M.; Zander, T.; Krywka, C.; Wang, M.; Dedinaite, A.; Claesson, P. M.; Willumeit-Römer, R.
Abstract : The development of a microfluidics setup for studying the interaction of complex solutions under varying shear conditions is presented. Abstract : The development of a dedicated small‐angle X‐ray scattering setup for the investigation of complex fluids at different controlled shear conditions is reported. The setup utilizes a microfluidics chip with a narrowing channel. As a consequence, a shear gradient is generated within the channel and the effect of shear rate on structure and interactions is mapped spatially. In a first experiment small‐angle X‐ray scattering is utilized to investigate highly concentrated protein solutions up to a shear rate of 300000 s −1 . These data demonstrate that equilibrium clusters of lysozyme are destabilized at high shear rates.